(Trans)missions : monasteries as sites of cultural transfers - Brenišínová, Monika (2022)
"(Trans)missions: Monasteries as Sites of Cultural Transfers focuses on the Catholic tradition of consecrated life (vita religiosa) from the High Middle Ages to the present. It gathers papers by authors from various disciplinary backgrounds, in particular art history, history, anthropology and translation studies. Finally, it includes two short reports on Czech projects on monastic topics. The chronological and geographical scope of the book is focused on the Western tradition from the High Middle Ages up to the present, specifically in the territory of Central Europe and Spain along with its overseas colonies. The region of Central Europe was interconnected with the Spanish Empire through the Austrian and Spanish Habsburgs, allowing the given topic to be studied in a broader international context, and to involve the Central European and Spanish territories in the global flow of information, thus incorporating the regional and national histories of individual European countries into global history. This involvement is also enabled by the study of interconnecting themes, such as cultural transfers within and between the Old and the New World, information flows between the Spanish and Austrian Habsburgs, the processes of individual and social identity formation, representation and othering of women, and the missionary activities of mendicant orders in the New World, together with their translation practices; and by the contextualization of monastic history and related themes within the processes of European internal and external colonization and evangelization."